Stability of Alugbati (Basella rubra) berry anthocyanin - Manucat, Novalyn Basco
ABSTRACT Anthocyanins of alugbati (Basella rubra) berries were extracted using acidified methanol and concentrated using a rotavapor. Berries were screened using total soluble solids (°Bx) and pH measurements. The stability of the anthocyanins as a function of varying substrate pH (pH 3.0, 7.0 and 9.0), processing condition (unpasteurized, pasteurized at 72°C for 15 seconds and thermally processed at 100°C for 10 minutes) and storage temperature (chilled condition, 10°C) was determined. Absorbance at 400 to 700 nm of the treated samples was obtained to determine the effect of the treatments. Color properties including L* (lightness), a* (redness and greenness, for negative values) and b* (blueness and yellowness, for negative values) of the treated samples were also measured. Acceptance and intensity scaling tests were done to evaluate the overall characteristics, color, intensity and evenness of the color. Results of the study demonstrated that the alugbati berry anthocyanin was stable at pH 3.0, pasteurization (72°C for 15 sec) and chilled condition (10°C). Alugbati berry anthocyanin in acidic and pasteurized condition was like moderately by the panelists. Therefore, alugbati berry anthocyanin as violet colorant can be a natural food color,especially to foods that require acidic condition and low processing temperature.